2022
DOI: 10.1038/s41467-022-31485-z
|View full text |Cite|
|
Sign up to set email alerts
|

Immunogenicity and reactogenicity of SARS-CoV-2 vaccines BNT162b2 and CoronaVac in healthy adolescents

Abstract: We present an interim analysis of a registered clinical study (NCT04800133) to establish immunobridging with various antibody and cellular immunity markers and to compare the immunogenicity and reactogenicity of 2-dose BNT162b2 and CoronaVac in healthy adolescents as primary objectives. One-dose BNT162b2, recommended in some localities for risk reduction of myocarditis, is also assessed. Antibodies and T cell immune responses are non-inferior or similar in adolescents receiving 2 doses of BNT162b2 (BB, N = 116… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
129
3

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 52 publications
(138 citation statements)
references
References 73 publications
6
129
3
Order By: Relevance
“…Although heterologous boosting has been reported to induce stronger cellular immune responses [44,45], our study showed the opposite. Moreover, cellular immunity was not signi cantly reactive in comorbidities (hypertension, heart disease, or diabetes mellitus), thus increasing the severity of infection with SARS-CoV-2 and mortality [46, 47,48,49,50].…”
Section: Discussioncontrasting
confidence: 79%
“…Although heterologous boosting has been reported to induce stronger cellular immune responses [44,45], our study showed the opposite. Moreover, cellular immunity was not signi cantly reactive in comorbidities (hypertension, heart disease, or diabetes mellitus), thus increasing the severity of infection with SARS-CoV-2 and mortality [46, 47,48,49,50].…”
Section: Discussioncontrasting
confidence: 79%
“… 39 Further, our results may not be generalisable to special patient populations in China, such as immunocompromised individuals, adolescents or pregnant women. However, it has been reported that in general, immunocompromised individuals are less likely to develop vaccine antibody responses compared with healthy subjects, 40 , 41 and may therefore need a different vaccination schedule. Also, a prior study conducted in Hong Kong found that immunogenicity responses of adolescents after two doses of BNT162b2 were non-inferior to adults.…”
Section: Discussionmentioning
confidence: 99%
“…Also, a prior study conducted in Hong Kong found that immunogenicity responses of adolescents after two doses of BNT162b2 were non-inferior to adults. 41 Although global studies showed that BNT162b2 vaccination in special patient populations was generally safe and generated protection from COVID-19 infection, more studies are needed to explore their use in special patient populations in China. Our study cohort, while of a reasonable size, does represent a small sample of the Chinese population and, therefore, studies with larger sample sizes and utilising more study sites would be useful to confirm our findings.…”
Section: Discussionmentioning
confidence: 99%
“…In-house WT S-RBD IgG enzyme-linked immunosorbent assay (ELISA) were carried out as previously published. 13,16 sVNT was conducted as per manufacturer's instructions (GenScript Inc, Piscataway, USA). 16 Cellular Primary outcomes on cellular immunogenicity included antiviral cytokine-expressing (IFN-γ + or IL-2 + ) helper (CD4 + ) or cytotoxic (CD8 + ) T cell responses against SARS-CoV-2 S (and N and M) proteins.…”
Section: Humoralmentioning
confidence: 99%
“…They were examined by intracellular cytokine staining on flow cytometry after stimulation with SARS-CoV-2 15-mer peptide pool(s) (Miltenyi Biotec, Bergisch Gladbach, Germany) as described previously. 13,14,17 SARS-CoV-2 S peptide pool was used for BNT162b2 while S, N and M peptide pools were used for CoronaVac as it is an inactivated whole-virus vaccine. Frequencies of T cell responses against S, N and M peptide pools were summated for CoronaVac.…”
Section: Humoralmentioning
confidence: 99%